Employing an ethical approach to writing in academic settings - Duzhyk, Nataliia (My University, 2020)
The paper studies the theoretical underpinning of writing guided by an ethical approach in an academic setting. A particular attention is paid to Sandra Stotsky’s framework which can be applied to students’ training in writing fundamentals and ethical thinking. Following the latest trends towards incorporating social issues into the classroom, the paper focuses on methodologies relevant to Ukrainian universities. Examples demonstrate how to apply an ethical approach to composing texts. У статті досліджуються теоретичні основи розвитку письмового мовлення у вищій школі з етичного погляду. Особлива увага приділяється моделі Стоцької (Stotsky), яка може застосовуватися у вивченні основ академічного письма та розвитку етичного мислення. Відстежуючи сучасні тенденції, що полягають в інтеграції соціально-вагомих питань в зміст курсів, стаття акцентує увагу на методології, застосовної до українських університетів. На прикладах показано, як розвивати письмове мовлення відповідно до етичного підходу.
Keywords: inclusiveness; academic writing; English language instruction; ethical approach; plagiarism; кафедра ділової іноземної мови та міжнародної комунікації; розвиток письмового мовлення; навчання англійської мови; етичний підхід; плагіат; інклюзивність